Variation in Activities of Non-Plasmin Fibrinolytic Proteinase and Plasminogen-Activator in the Lung and Spleen Induced by Bacterial Endotoxin in Rats with Special Reference to the Effects of MD-805 - Okamoto, U; Nagamatsu, Y; Horie, N; Yamamoto, J; Sasaki, K (Thrombosis and Haemostasis, 1985)
The behavior of direct fibrinolytic (non-plasmin) proteinase activity and plasminogen-activator activity in the lung and spleen was investigated in rats after a single intravenous injection of bacterial endotoxin, and the influence of thrombin inhibitors on the effects of the endotoxin was assessed.The non-plasmin fibrinolytic activitiy was markedly increased following a decrease of plasminogen-activator in the lung. In addition, variations in hematological parameters, i.e. a decrease of platelet count, fibrinogen level and antithrombin III, and an increase of blood urea nitrogen and euglobulin fibrinolytic activity, were induced by the injection, indicating the occurrence of disseminated intravascular coagulation.In comparative studies on the effects of the endotoxin injection and thrombin infusion, in the lung and spleen an increase of fibrinolytic proteinase activity was induced in a similar manner; the plasminogen-activator activity in the lung was decreased by the endotoxin injection but not decreased by the thrombin infusion.In prevention studies with heparin and MD-805, the latter was found to prevent the decrease of either fibrinogen or platelet count. However, the former failed to prevent the decrease of platelet count although that of the fibrinogen level was prevented. Heparin and MD-805 exerted no preventive effect on the endotoxin-induced variations of proteinase activity and plasminogen-activator activity in the lung.
Keywords: Non-plasmin fibrinolytic proteinase; Plasminogen-activator; Endotoxin; MD-805; Synthetic thrombin inhibitor